Rapamycin Promotes Expansion of Functional CD4+CD25+FOXP3+ Regulatory T Cells of Both Healthy Subjects and Type 1 Diabetic Patients - Battaglia, Manuela; Stabilini, Angela; Migliavacca, Barbara; Horejs-Hoeck, Jutta; Kaupper, Thomas; Roncarolo, Maria-Grazia (The Journal of immunology (1950), 2006)
CD4+CD25+FOXP3+ T regulatory cells (Tregs) are pivotal for the induction and maintenance of peripheral tolerance in both mice and humans. Rapamycin has been shown to promote tolerance in experimental models and to favor CD4+CD25+ Treg-dependent suppression. We recently reported that rapamycin allows in vitro expansion of murine CD4+CD25+FoxP3+ Tregs, which preserve their suppressive function. In the current study, we show that activation of human CD4+ T cells from healthy subjects in the presence of rapamycin leads to growth of CD4+CD25+FOXP3+ Tregs and to selective depletion of CD4+CD25− T effector cells, which are highly sensitive to the antiproliferative effect of the compound. The rapamycin-expanded Tregs suppress proliferation of both syngeneic and allogeneic CD4+ and CD8+ T cells. Interestingly, rapamycin promotes expansion of functional CD4+CD25+FOXP3+ Tregs also in type 1 diabetic patients, in whom a defect in freshly isolated CD4+CD25+ Tregs has been reported. The capacity of rapamycin to allow growth of functional CD4+CD25+FOXP3+ Tregs, but also to deplete T effector cells, can be exploited for the design of novel and safe in vitro protocols for cellular immunotherapy in T cell-mediated diseases.